1993
DOI: 10.1093/nar/21.12.2853
|View full text |Cite
|
Sign up to set email alerts
|

Site-directed cross-linking of mRNA analogues to 16S ribosomal RNA; a complete scan of cross-links from all positions between ‘+ 1’ and ‘+ 16’ on the mRNA, downstream from the decoding site

Abstract: mRNA analogues containing 4-thiouridine residues at selected sites were used to extend our analysis of photo-induced cross-links between mRNA and 16S RNA to cover the entire downstream range between positions +1 and +16 on the mRNA (position +1 is the 5'-base of the P-site codon). No tRNA-dependent cross-links were observed from positions +1, +2, +3 or +5. Position +4 on the mRNA was cross-linked in a tRNA-dependent manner to 16S RNA at a site between nucleotides ca 1402-1415 (most probably to the modified res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
33
0

Year Published

1994
1994
2007
2007

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(40 citation statements)
references
References 12 publications
7
33
0
Order By: Relevance
“…We have undertaken a study of the conformation of the 39 major domain of 16S rRNA, in the absence of proteins, using a site-directed crosslinking method+ The crosslinks were generated in a high-ionic strength buffer, where this domain adopts a conformation recognized by the ribosomal proteins+ The importance of rRNA warrants a detailed investigation of its higher-order structure+ rRNA may have functioned at a time without the aid of proteins (Noller, 1993), and a large body of evidence supports the direct role of rRNA in protein synthesis )+ A report by Nitta et al+ (1998a,b) recently suggested that in vitro-transcribed naked 23S rRNA could have peptidyl transferase activity+ Previously, Purohit & Stern (1994) had shown that a fragment of 16S rRNA corresponding to the decoding center of 16S rRNA had the capacity to interact with mRNA, tRNA anticodon stem-loop, and aminoglycoside antibiotics such as neomycin in a similar way as 16S rRNA within 30S subunit, indicating that this fragment is able to perform some of the functions of the ribosome+ Several of the crosslinks we observed in the free 39 major domain are in agreement with proximity relationships that have been observed within the 30S subunit+ Crosslink I, which joins position 993 to a segment encompassing nt 1205-1215, is consistent with a previous UV crosslink joining positions 991-1212+ This crosslink was identified in 16S rRNA within the 30S subunit first by Stiege et al+ (1988) and, later on, with a higher resolution, by Wilms et al+ (1997)+ Also, crosslink IV, which links the upper stem of helix 34 to helix 28 in the free domain, agrees with a proximity relationship demonstrated between positions 1196 and 1395 in 16S rRNA within the 30S subunit, using crosslinking with mRNA analogs (Rinke-Appel et al+, 1993;Juzumiene et al+, 1995;Sergiev et al+, 1997) or cleavage with mRNA modified with phenanthroline (Bucklin et al+, 1997 to nt 934-938, a segment connecting helices 28 to 29, and also to nt 1229-1233 in helix 30+ The neighboring nucleotide G1338 is required for tRNA binding at the P site (von Ahsen & Noller, 1995) and has been crosslinked to the anticodon loop of P-site-bound tRNA, while position 936 has been crosslinked to the anticodon loop of tRNA bound at the A site (Döring et al+, 1994)+ The obvious proximity between the anticodon loops of A-siteand P-site-bound tRNAs is in complete agreement with crosslink VII+ As to crosslink VIII, which links position 1337 to the 1230 region, Noller and his coworkers also observed that these regions are proximal by probing 16S rRNA within the 30S subunit with hydroxyl radicals generated either with a tRNA anticodon stem-loop analog bound to the P site or with elongation factor G (Joseph et al+, 1997;Wilson & Noller, 1998)+ On the whole, our results strongly suggest that, when in solution in reconstitution buffer, the free RNA domain adopts a conformation that is similar to that within the 30S subunit+ Nevertheless, this conformation probably differs in details from that within the 30S subunit+ Ribosomal proteins have been shown to cause several local adjustments in the conformation of 16S rRNA, and they appear to stabilize rRNA tertiary structure and FIGURE 5. Examples of ...…”
Section: Discussionsupporting
confidence: 88%
“…We have undertaken a study of the conformation of the 39 major domain of 16S rRNA, in the absence of proteins, using a site-directed crosslinking method+ The crosslinks were generated in a high-ionic strength buffer, where this domain adopts a conformation recognized by the ribosomal proteins+ The importance of rRNA warrants a detailed investigation of its higher-order structure+ rRNA may have functioned at a time without the aid of proteins (Noller, 1993), and a large body of evidence supports the direct role of rRNA in protein synthesis )+ A report by Nitta et al+ (1998a,b) recently suggested that in vitro-transcribed naked 23S rRNA could have peptidyl transferase activity+ Previously, Purohit & Stern (1994) had shown that a fragment of 16S rRNA corresponding to the decoding center of 16S rRNA had the capacity to interact with mRNA, tRNA anticodon stem-loop, and aminoglycoside antibiotics such as neomycin in a similar way as 16S rRNA within 30S subunit, indicating that this fragment is able to perform some of the functions of the ribosome+ Several of the crosslinks we observed in the free 39 major domain are in agreement with proximity relationships that have been observed within the 30S subunit+ Crosslink I, which joins position 993 to a segment encompassing nt 1205-1215, is consistent with a previous UV crosslink joining positions 991-1212+ This crosslink was identified in 16S rRNA within the 30S subunit first by Stiege et al+ (1988) and, later on, with a higher resolution, by Wilms et al+ (1997)+ Also, crosslink IV, which links the upper stem of helix 34 to helix 28 in the free domain, agrees with a proximity relationship demonstrated between positions 1196 and 1395 in 16S rRNA within the 30S subunit, using crosslinking with mRNA analogs (Rinke-Appel et al+, 1993;Juzumiene et al+, 1995;Sergiev et al+, 1997) or cleavage with mRNA modified with phenanthroline (Bucklin et al+, 1997 to nt 934-938, a segment connecting helices 28 to 29, and also to nt 1229-1233 in helix 30+ The neighboring nucleotide G1338 is required for tRNA binding at the P site (von Ahsen & Noller, 1995) and has been crosslinked to the anticodon loop of P-site-bound tRNA, while position 936 has been crosslinked to the anticodon loop of tRNA bound at the A site (Döring et al+, 1994)+ The obvious proximity between the anticodon loops of A-siteand P-site-bound tRNAs is in complete agreement with crosslink VII+ As to crosslink VIII, which links position 1337 to the 1230 region, Noller and his coworkers also observed that these regions are proximal by probing 16S rRNA within the 30S subunit with hydroxyl radicals generated either with a tRNA anticodon stem-loop analog bound to the P site or with elongation factor G (Joseph et al+, 1997;Wilson & Noller, 1998)+ On the whole, our results strongly suggest that, when in solution in reconstitution buffer, the free RNA domain adopts a conformation that is similar to that within the 30S subunit+ Nevertheless, this conformation probably differs in details from that within the 30S subunit+ Ribosomal proteins have been shown to cause several local adjustments in the conformation of 16S rRNA, and they appear to stabilize rRNA tertiary structure and FIGURE 5. Examples of ...…”
Section: Discussionsupporting
confidence: 88%
“…3) in a region believed to be involved in recognition of peptide chain termination codons (24,25). This region has been directly linked to the decoding site on the ribosome by cross-links from U1052, which is adjacent to m 2 G1207 on the opposite strand to the A site codon of mRNA (26) and from A1196, 11 nucleotides away on the same strand, to the next downstream mRNA codon (10). However, no specific role for m 2 G1207 is known in chain termination or codon recognition or, for that matter, in any other function of the ribosome.…”
Section: Substrate Specificity and Mg 2ϩmentioning
confidence: 99%
“…Crosslink frequency is scored as (ϩ) moderate, (ϩϩ) strong, (ϩϩϩ) very strong+ Distance estimates are based on distances of the crosslinking group from the phosphate of G9: for constructs Ϫ5, ϩ1, ϩ5, ϩ8 these are 88 Å, 58 Å, 34 Å, and 16 Å+ The constructs ϩ14 and ϩ21 have defective function or structure and crosslinks that occur only in them are not used for distances estimates+ The list shows the sites in groups of nucleotide positions that are close in the secondary structure+ ϩ8 constructs+ There is one additional site 1149-1151 that is crosslinked with only the ϩ8 construct (Table 3)+ There has been only circumstantial evidence for the location and arrangement of these sites+ Helix H34, adjacent to H35-H37, is positioned close to the decoding region in the front middle of the subunit based on results that involve crosslinks from position ϩ5 mRNA to nucleotides 1052 (Rinke-Appel et al+, 1993), from ϩ11 in the mRNA to position 1196 (Juzumiene et al+, 1995), from ϩ2 in the mRNA to nucleotide 1080 in 30S subunits reconstituted with synthetic 16S rRNA (D+ Juzumiene, unpubl+ results), and from ϩ2 in the mRNA to 1167-1168 in native 30S subunits (D+ Juzumiene, unpubl+ results)+ Other mRNA crosslinking sites in the region occur at 1156 (Bhangu & Wollenzien, 1992) and 1131-1132 (Wollenzien et al+, 1991), but the location of these sites with respect to the decoding site was not known+ A site-directed cleavage experiment was done in which the BABE reagent was tethered to position 922; it cleaved nucleotides in the interval 1192-1198 (Samaha et al+, 1999)+ This places the 1192-1198 region not more than 22 Å from 922+ In another sitedirected cleavage experiment, in which Cys 21 of protein S5 was modified with the BABE reagent, cleavage in the 16S rRNA was observed in the intervals 1062-1066 and 1090-1096 as well as at sites around the central pseudoknot at 920, 1400, 535, and 420 regions+ This indicates that part of domain 3 is close to the position of S5 in center of the subunit + Nucleotides in the 1060-1110 interval have also been positioned in the upper left of the subunit above the constriction that separates the body from the head subunit based on their association with S2 and S3 (Stern et al+, 1989; and the positions of those proteins (Capel et al+, 1987)+ The surprising part of the APA crosslinking result is the very small distance between the sites 1071-1072, 1080-1082, 1092, and 1149-1151 in this region and G9+ This indicates the H35, H36, and H37 helices have to be very close to the middle part of the subunit+ There has been speculation about the flexibility of the head of the subunit around helix 28 (see Wilson & Noller, 1998)+ A rotational motion of the subunit head would allow the H35 top H37 helices to be close to the front middle of the subunit and this may account for the APA crosslinking to these sites+ Several sites in the decoding region are subject to crosslinking in a way that suggests their locations and orientations+ Nucleotides 1492-1493 are crosslinked in constructs Ϫ5 to ϩ8, but there is somewhat of a reduction in the frequency for the ϩ8 crosslink (see Fig+ 2), so we conclude the distance for 1492-1493 to G9 is about 16 Å+ 1400-1401 and 1413 are not crosslinked at the same frequency as 1492-1493 in the ϩ8 construct, so they both may be somewhat greater distance (16-34 Å)+ The sites 1400-1401 and 1413 are each about one half turn away from 1492-1493 and if the region were helical, all...…”
Section: Discussionmentioning
confidence: 99%